Serum concentrations of perfluorinated compounds among children living in Sicily (Italy). (1st December 2018) - Ledda, Caterina; La Torre, Giuseppe; Cinà, Diana; Paravizzini, Gianluca; Vitale, Ermanno; Pavone, Piero; Iavicoli, Ivo; Rapisarda, Venerando
Highlights: Low PFCs concentration in children living in Sicily. PFSO concentration is higher in girls. Maternal parity is significantly associated with PFDA and PFHxS. Months of breastfeeding is significantly correlated with PFUnDA. Abstract: Perfluorinated compounds (PFCs) are a large group of man-made chemicals characterized by a completely fluorinated hydrophobic linear carbon chain attached to a hydrophilic head. The presence of PFCs has been related with various adverse effects on several organs and systems. 61 children (6–11 years of age) living in Sicily underwent medical examination and blood and urine routinary tests, as well as the serum concentration of 16 PFCs. These compounds (∑PFCs = 5.888 ng/mL, range 1.035–12.94 ng/mL) were widely detected in the samples of all children, showing that they had been extensively exposed to PFCs, especially perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), perfluorohexanesulfonate (PFHxs) and perfluorodecanoic acid (PFDA). In addition, long-chained PFCs were found in children's blood correlated with short-chained ones. Perfluorodecanoic acid (PFDA) (beta=−0.114) and PFHxS (beta = 0.003) levels were correlated with maternal parity; while the "months of breastfeeding" variable is correlated with perfluoroundecanoic acid (PFUnDA) concentrations (beta = 0.008). Female gender is negatively associated with PFOS (beta = 0.008). The adverse health effects of PFCs on young children should be noted, due to their growing phase. Therefore, further studies are needed to monitor and address adverse health outcomes of PFCs on children, especially those living in industrial regions.